EFFECT OF SCHOOL CLIMATE ON TEACHING AND LEARNING OF PHYSICS IN SENIOR SECONDARY - T., Adolphus; T.S.B, Aderonmu; N.B, Naade (International Journal of Online and Distance Learning, 2021)
Purpose: The study investigated the effect of school climate on teaching and learning of physics in senior secondary schools. Methodology: The mixed research design, specifically descriptive and exploratory analysis method was employed for the study. 14 Physics teachers and 248 Physics students were purposively selected from four secondary schools in Rivers State, Nigeria. Instruments for data collection includes Questionnaire for Physics Teachers (QPT), Questionnaire for Physics Students (QPS) and two semi-structured interview schedules which are Interview Schedule for Teachers (ISfT) and the Interview Schedule for Students (ISfS). Data were analyzed using mean and percentage for the research questions while hypotheses were tested at 0.05 level of significance using t-test. Results: The findings of the study revealed that although Physics teachers enjoy a fairly good working relationship with their students, both teachers and students maintained that their school climate were not friendly and conducive for teaching of Physics. The study further revealed that there were no significant differences between male and female Physics teachers and students on their mean responses on school climate related factors affecting the teaching and learning of Physics. Unique contribution to theory and practice: The study recommended exigent need for synergy among all stakeholders in the secondary school to encourage the prevalence of harmonious relationship that will enhance effective teaching and learning of Physics among others.